2009
DOI: 10.2134/agronj2007.0144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation with Secondary Treated Effluent on Essential Oil, Antioxidant Activity, and Phenolic Compounds in Oregano and Rosemary

Abstract: Shortage of water throughout the world dictates utilization of marginal water for irrigation. Treated urban wastewater is a common alternative water source for irrigation in arid and semiarid regions. In this study we aimed to evaluate the eff ect of irrigation with secondary-treated effl uent on plant development, essential oil yield, antioxidant activity and selected antioxidant phenolic compounds in two commercial cultivars of the aromatic species, oregano (Origanum vulgare L.) and rosemary (Rosmarinus offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 45 publications
5
26
2
Order By: Relevance
“…S2B, p = 0.001) and increased during the growing season (from 1.2-5 ms cm −1 , R 2 = 0.13). This finding is similar to those reported by previous studies that applied TWW irrigation in Israel (Bernstein et al, 2009;Sacks and Bernstein, 2011). There was no effect of irrigation water or the interaction of time and irrigation water.…”
Section: Soil Chemical and Physical Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…S2B, p = 0.001) and increased during the growing season (from 1.2-5 ms cm −1 , R 2 = 0.13). This finding is similar to those reported by previous studies that applied TWW irrigation in Israel (Bernstein et al, 2009;Sacks and Bernstein, 2011). There was no effect of irrigation water or the interaction of time and irrigation water.…”
Section: Soil Chemical and Physical Propertiessupporting
confidence: 92%
“…1 and 2, Table 2). The accumulation and persistence of fecally sourced microbes from WW in soil is one of the major concerns associated with WW irrigation (Bernstein et al, 2009), and has been shown to occur under simulated conditions (Bernstein et al, 2007;Monaghan and Hutchison, 2012;Ramirez et al, 2009). Yet in this study utilizing TWW under field conditions, no evidence for this phenomenon was found.…”
Section: Discussionmentioning
confidence: 99%
“…It contradicts however previous reports which showed either no effects, as in several aromatic plants (Bernstein et al 2009), or even indicated yield increases in various crops (Chakrabarti 1995;Al-Nakshabandi et al 1997;Marecos do Monte MHF 1998;Negahban-Azar et al 2013;Peña et al 2014). The development of tomato plants, a species with low salt tolerance (Cuartero and Fernández-Muñoz 1999), was probably impaired by irrigation with WW, which had higher salinity than DW, especially when the plants were further stressed by pesticide addition.…”
Section: Plant Quality Indicatorscontrasting
confidence: 86%
“…The relative contribution of each source to the sewage is site specific but it is probably safe to say that in the majority of cases, in mass terms, Na þ is by far the most dominant cation that is added to the sewage. The reports on sodium addition due to domestic or mixed domestic/industrial water use vary considerably: While some sources report the addition to be in the range 40 -70 mg L 21 (Pettygrove & Asano 1985; Tchobanoglous et al 2003) or lower (Mercado & Banin 1994), other sources report on an additional Na þ concentration of , 115 mg L 21 (Rebhun 1965;Bernstein et al 2009) and a recent paper reports on Na þ addition in the range 200 to 250 mg L 21 (Friedman et al 2007).…”
Section: The Sar Problemmentioning
confidence: 99%